A systematic review and meta‐analysis of randomized controlled trials of "on‑demand" use of tramadol vs "on‑demand" use of paroxetine in the management of patients with premature ejaculation. Issue 11 (16th September 2021) - Tan, Haotian; Zhou, Zhongbao; Cui, Yuanshan; Feng, Fan; Zhang, Yong
Abstract: Aim: To evaluate the effect of "on‑demand" use of tramadol vs "on‑demand" use of paroxetine in the management of patients with premature ejaculation (PE). Materials and Methods: A systematic search of PubMed, EMBASE, Cochrane Library databases and original references of the included articles was performed. PRISMA checklist was followed. The Cochrane Handbook was used to evaluate the quality of the included research. Results: A total of seven articles including 663 patients were studied. The results indicated that patients who received on‐demand therapy of tramadol or paroxetine showed significant improvement compared with those treated with placebo, as assessed by intravaginal ejaculatory latency time (IELT) ( P  < .00001 and P  = .02, respectively) and sexual satisfaction score ( P  < .00001 and P  < .00001, respectively). Furthermore, Patients who were treated with on‑demand tramadol had a better effect than those treated with on‑demand paroxetine in respect of IELT ( P  = .01) and sexual satisfaction score ( P  = .03). With regard to safety, the most common adverse event for the tramadol group was sleep disturbance and the most common adverse event for the paroxetine group was a headache. No serious adverse event was observed in both groups. Conclusions: Compared with placebo, on‐demand therapy of tramadol or paroxetine showed a better improvements in IELT and sexual satisfaction scores. Besides, on‑demand tramadol revealed a better effect than on‑demand paroxetine for patients with PE, and patients in both groups showed good tolerance.